High-efficiency quantum dot light-emitting diodes based on Li-doped TiO2 nanoparticles as an alternative electron transport layer. Issue 5 (28th January 2021) - Kim, Moonbon; Lee, Nayeon; Yang, Joong Hwan; Han, Chang Wook; Kim, Hyun-Min; Han, Wooje; Park, Hyung-Ho; Yang, Heesun; Kim, Jiwan
Abstract : We report high-efficiency quantum dot light-emitting diodes (QLEDs) with Li-doped TiO2 nanoparticles (NPs) as an alternative electron transport layer (ETL). Abstract : We report high-efficiency quantum dot light-emitting diodes (QLEDs) with Li-doped TiO2 nanoparticles (NPs) as an alternative electron transport layer (ETL). Colloidally stable TiO2 NPs are applied as ETLs of inverted structured QLEDs and the effect of the addition of lithium (Li) to TiO2 NPs on device characteristics is studied in detail. Compared to pristine TiO2 NPs, Li-doped ones are found to be beneficial for the charge balance in the emitting layer of QLEDs mainly by means of their upshifted conduction band minimum, which in turn limits electron injection. A green QLED with 5% Li-doped TiO2 NPs produces a maximum luminance of 169 790 cd m −2, an EQE of 10.27%, and a current efficiency of 40.97 cd A −1, which indicate the best device performances to date among QLEDs with non-ZnO inorganic ETLs. These results indicate that Li-doped TiO2 NPs show great promise for use as a solution-based inorganic ETL for future QLEDs.